The Study of Upper Secondary Level Learners’ Behavior Returning to Classroom (On-site) During the Ease of the Covid-19 Pandemic - Manchat, Hatthaya (An Online Journal of Education, 2024)
This research delves into the behavior of upper secondary school students in learning and living during the COVID-19 easing phase, focusing on a large school in Nonthaburi province. Employing a mixed methods research approach, it combines quantitative research, involving 311 participants, and qualitative research, involving 15 individuals, The research instruments were implemented by questionnaires and interviews. The data analysis was used the descriptive statistic, Pearson Correlation and thematic analysis. The findings can be summarized as follows: 1) the study of behaviors of upper secondary school students found that the students exhibited the highest levels of cooperation (M = 4.21, SD = 1.0) with average levels classified as high. The next most common behavior was listening to authority (M = 3.70, SD = 0.9), also rated as high. 2) the study of factors influencing the behavior of students showed that educational management had the greatest impact on student behavior. During the online learning period, the average impact was high (M = 3.80, SD = 1.1), and it remained high during the on-site learning period (M = 4.00, SD = 1.1). 3) Pearson’s correlation coefficients revealed strong positive links between educational management, cooperative behavior, and teacher attitudes during both online (.376) and on-site learning (.495).